A survey of records management practices in selected colleges and universities in Quezon City and Manila - Granda, Yolanda Canlas (1981)
The study is intended primarily to find out the existing practices, programs, conditions, and problems of records operations in eleven colleges and universities in Quezon City and Manila and to propose necessary measures towards their improvements. It was carried out to respond to the expressed needs of archivists that the development of a comprehensive archives requires the support of an efficient and cost-effective records management program.